Specifics in the Management of Sport Climbing in European region after it became the Olympic Sport - Michalková, Anna (2022)
The aim of the work was to find out how the way of managing national sport climbing federations (NFs) in Europe has changed after sport climbing became the Olympic sport in 2016. The International Federation of Sport Climbing (IFSC) was expected to have major influence on the development of sport management as it led the process of addi-tion of the sport into the Olympic programme. After the analysis of survey of European NFs, the assumption that NFs are heavily influenced by their international federation was confirmed. IFSC is governed with reliance to general theory of sport management and evolves each aspect of sport management to certain level. In the field of sport develop-ment, it inspires national federations, but does not fully follow the scheme of the devel-opment of sport. In conformity with the goals IFSC maintains the international competi-tion system. On the contrary, national federations in Europe must develop all aspects of sport management within their organization. Unlike the IFSC, they must also develop the sport in its full extent and the conditions for its implementation in their countries - creat-ing a sports base, supporting talented athletes and implementing competition systems in line with changes at the international level. According to a survey of athletes, parents, coaches and NF representatives, many national federations are following the changes that the IFSC is introducing at the international level.